The Ideological Categories in the Discourses of World Health Organization on Covid-19 - نغم حسين; علي فارس (آداب الكوفة, 2023)
On 31 December 2019, WHO received information from National Health Commission concerning the outbreak of Covid-19 which was identified by the Chinese authorities. The WHO depends to a great extent on its announcements and instructions on Chinese authorities’ declaration.  Consequently, positive and negative announcements and strategies are adopted in dealing with this pandemic. This causes a great extent of fear and confusion for people around the world despite all the efforts that WHO to pass this crucial period successfully and safely. The present study is one of the first studies that seeks to offer critical discourse analysis, description, interpretation, and explanation of ideological categories of institutional discourse, and more specifically of WHO on Covid-19 by using Van Dijk’s Three-Dimensional Model of Ideology (2004). It is found that WHO focuses on certain ideological categories such as repetition, actor description, authority, hyperbole, burden, evidentiality, and number game more than other categories.  It is also found that these ideological categories should be based on scientific, psychological, cognitive, social, and cultural perspectives and not just numbers, authority, hyperbole, etc. because they are used to persuade different people around the world with different cultures and they may affect those people lives positively or negatively.